Reforming Land Public Interest Litigation in China: Addressing Legal and Practical Barriers - Jing Zhang; Shuchen Tang; Yongcun Cui; Aitong Ji (Land)
Land public interest litigation (LPIL) has emerged as a vital mechanism for addressing China’s land crisis. It serves dual purposes: mitigating the tragedy of the commons and safeguarding the legitimate rights of vulnerable groups reliant on land. Over the past decade, China’s LPIL framework has evolved significantly, with enhanced legislation and consistent judicial practices contributing to the prevention of further land degradation. However, an empirical analysis of 208 LPIL cases reveals a judiciary-led litigation model, with procuratorial bodies initiating 94.71% of cases, while non-governmental organizations (NGOs) and individuals account for only 3.85% and 0%, respectively. This narrow plaintiff base, coupled with significant regional disparities—74.52% of cases concentrated in the top ten provinces—and a mere 25% filing rate for administrative cases, limits the system’s effectiveness. These constraints hinder vulnerable groups’ ability to protect their rights and obscure systemic issues underlying efficient operations. To advance LPIL, China must expand plaintiff eligibility, empower NGOs, and clarify departmental boundaries. These reforms can enhance land governance, ensure equitable resource management, and contribute to sustainable development.